МАҚСУД ШАЙХЗОДА - Abdujalilova Moxinur Valijon qizi (Journal of new century innovations, 2023)
Annotation: In this article, mainly samples of the unique, lush creativity of the Uzbek folk poet Maqsud Shaikhzoda were drawn into the analysis.